Makanan Ritual dan Makna Simboliknya: Analisis Tradisi Kuliner Sego Langgi di Lamongan, Indonesia: Ritual Meals and Its Symbolic Meaning: Analyses of Culinary Tradition Sego Langgi in Lamongan, Indonesia - Muhammad Hilman Hirzi; Rossana Farah Abida; Rahmat; Wahidah Zein Br Siregar (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
This article examines the symbolic meaning of Sego Langgi as a culinary tradition of the rural Muslim people of Sendangduwur Village, Lamongan, Indonesia, particularly focusing on the religious values, communal solidarity, and cultural identity contained therein. This research used a qualitative approach with ethnographic methods, and combined Clifford Geertz's theory of cultural symbolism, Claude Lévi-Strauss's theory of structuralism, Herbert Blumer's theory of symbolic interactionism, Pierre Bourdieu's theory of cultural inheritance, and Stuart Hall's theory of cultural identity. Obtaining data through participant observation, in-depth interviews, and visual and textual documentation, the research showed that Sego Langgi is not only a ritual meals, but also a medium for inheriting values carried out performatively and informally through cross-generational involvement in the tradition. It also reflects the values of help, simplicity, and respect towards ancestors. Amidst the modernization, the community continues to maintain its existence through the adaptation of digital media as a tool for documentation and preservation. Finally, this article’s scientific contribution lies in enriching local cultural-based culinary studies with a multidisciplinary theoretical approach, as well as in affirming the importance of tradition as a space for the production of values and identity in rural Muslim communities.